Detection of anisakis using multi-wavelength analysis of photoacoustic signal - Yoshida, Nao; Namita, Takeshi; Shiina, Tsuyoshi; Yamakawa, Makoto; Kondo, Kengo (Transactions of Japanese Society for Medical and Biological Engineering, 2021)
Consumption of raw fish products containing anisakis can engender a severe human disease known as anisakidosis. Conventional screening methods such as candling are not accurate or sufficiently sensitive to detect parasites that are embedded deeply in fish muscle. To resolve these shortcomings, we devised a method using photoacoustic imaging. As a fundamental study, we measured photoacoustic spectra of anisakis and mackerel (300-700 nm wavelengths). The spectrum for anisakis decreases monotonically, although the spectrum of mackerel increases moderately in 375-400 nm and 490-540 nm. There was the difference in the intensity ratio of the photoacoustic signals of anisakis and mackerel at 375nm and 400 nm (I375 nm / I400 nm) and 490 nm and 530 nm (I490 nm / I530 nm). These analyses demonstrated the possibility of detecting anisakis in mackerel using multi-wavelength analysis at wavelengths of 375-400 nm and 490-540 nm.